RMSD analysis of structures of the bacterial protein FimH identifies five conformations of its lectin domain. Issue 4 (5th November 2019) - Magala, Pearl; Klevit, Rachel E.; Thomas, Wendy E.; Sokurenko, Evgeni V.; Stenkamp, Ronald E.
Abstract: FimH is a bacterial adhesin protein located at the tip of Escherichia coli fimbria that functions to adhere bacteria to host cells. Thus, FimH is a critical factor in bacterial infections such as urinary tract infections and is of interest in drug development. It is also involved in vaccine development and as a model for understanding shear‐enhanced catch bond cell adhesion. To date, over 60 structures have been deposited in the Protein Data Bank showing interactions between FimH and mannose ligands, potential inhibitors, and other fimbrial proteins. In addition to providing insights about ligand recognition and fimbrial assembly, these structures provide insights into conformational changes in the two domains of FimH that are critical for its function. To gain further insights into these structural changes, we have superposed FimH's mannose binding lectin domain in all these structures and categorized the structures into five groups of lectin domain conformers using RMSD as a metric. Many structures also include the pilin domain, which anchors FimH to the fimbriae and regulates the conformation and function of the lectin domain. For these structures, we have also compared the relative orientations of the two domains. These structural analyses enhance our understanding of the conformational changes associated with FimH ligand binding and domain‐domain interactions, including its catch bond behavior through allosteric action of force in bacterial adhesion.